Validating the CRAFFT substance abuse screening test for adolescents in Colombia (2013)
Objectives: Evaluating the properties of the CRAFFT (mnemonic acronym of first letters of key words in the six screening questions) scale for substance abuse screeningin the Colombian adolescent population aged 14 to18 years-old. Methods: The criteria were validated by comparing the CRAFFT scale to the gold standard for identifying substance abuse (i.e. the clinical interview). A diagnostic test model was used for calculating the scale's sensitivity, specificity and predictive values. Results: The test revealed 0.95 sensitivity, 0.83 specificity, 0.85 PPV and 0.94 NPV (x2=187.87 and p less than 0.0005) for identifying dysfunctional use (frequent use, abuse and dependence), having a >2 score. Conclusions: The scale was seen to have great usefulness for psychoactive substance use screening. A cut-off point of 2 differentiated functional from dysfunctional use.